Socio-Legal Analysis of Age Restrictions in Cinema: A Hermeneutic Interpretation of Law Number 33/2009 - Maulidina, Citra Puspa; Wijaya, Widiastiana Vista; Sunarto, Shilvy Andini (COMMUSTY Journal of Communication Studies and Society, 2023)
This research discusses how Law No. 33 of 2009, especially article 7, which discusses the age classification or age of the audience by Film Show Companies (cinemas), where films with various themes and ratings are screened, a deep understanding of how cinemas maintain age classification so as not to be exposed to content that is not suitable for the age of the audience. The purpose of this research is to see how the role and responsibility of movie theaters in implementing Law No. 33 of 2009, especially article 7 and maintaining security, understanding related to the law. Because with the right understanding, it will affect the application of theaters to ensure that they operate in accordance with existing regulations. The research method uses Hermeneutic analysis, in hermeneutics there are three components, namely understanding, interpretation and application, which is related to the cinemas that have understood, interpreted and applied the age classification of the audience by the Film Show Company (cinema). The results showed that in its application, the movie theater has tried to apply the law in accordance with applicable regulations, but there are still many obstacles, especially from people who are less concerned about the shows they watch in terms of age classification. Theaters have tried to apply the law, but theaters are unable to control the application of the law to be applied. According to film observers, the law has been implemented by theaters, but the age category information displayed on plasma TVs is so small that not all viewers pay attention to the information. The Film Censorship Board does not specifically have the right to revise this law, from LSF's perspective, this is sufficient because everything has been regulated in detail. The public is encouraged to be more aware of Law No. 33 Year 2009, especially Article 7 which regulates the age classification of the audience.